1980
DOI: 10.1038/287740a0
|View full text |Cite
|
Sign up to set email alerts
|

Lignans in man and in animal species

Abstract: In our laboratories, for several years, two phenolic compounds have been detected during gas chromatographic-mass spectrometric analysis of urinary steroid extracts from human and animal species. Although features of the mass spectra of their trimethylsilyl (TMS) ether derivatives resembled those of oestrogens, they were atypical of steroids. The possibility that they were artefacts of the isolation procedures was discounted after careful studies with blanks, by varying the extraction method and because they w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
134
0
4

Year Published

1981
1981
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 275 publications
(139 citation statements)
references
References 10 publications
1
134
0
4
Order By: Relevance
“…The observations of a cyclic pattern of excretion of HBBL and HBBD during the menstrual cycle of humans [3,5,6 81 and monkeys [ 71 suggested initially that they were produced by the ovaries or influenced by ovarian function. Using the rat however, we have unequivocally demonstrated that lignans are not formed in the ovaries but are biosynthesised by intestinal bacteria, resembling therefore vitamin K synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The observations of a cyclic pattern of excretion of HBBL and HBBD during the menstrual cycle of humans [3,5,6 81 and monkeys [ 71 suggested initially that they were produced by the ovaries or influenced by ovarian function. Using the rat however, we have unequivocally demonstrated that lignans are not formed in the ovaries but are biosynthesised by intestinal bacteria, resembling therefore vitamin K synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…On a body weight basis the daily urinary excretion of the lignans HBBL and HBBD considerably exceeded (5-20-fold) the amounts found in humans [3,5,6] and there was some evidence to indicate a sex difference in the excretion of these compounds; female rats excreting larger amounts of HBBL and smaller amounts of the unknown diphenolic compound compared with male animals. Such differences are not uncommon in rats, steroid metabolism is characterised by qualitative differences between the male and female [ 151, however, in view of the limited number of measurements, additional data are required to confirm this observation.…”
Section: Conventional Ratsmentioning
confidence: 98%
See 3 more Smart Citations